Multidisciplinary Team-Based Approach for Comprehensive Preoperative Pulmonary Rehabilitation Including Intensive Nutritional Support for Lung Cancer Patients - Harada, Hiroaki; Yamashita, Yoshinori; Misumi, Keizo; Tsubokawa, Norifumi; Nakao, Junichi; Matsutani, Junko; Yamasaki, Miyako; Ohkawachi, Tomomi; Taniyama, Kiyomi (PLOS ONE, 2013)
Background To decrease the risk of postoperative complication, improving general and pulmonary conditioning preoperatively should be considered essential for patients scheduled to undergo lung surgery. Objective The aim of this study is to develop a short-term beneficial program of preoperative pulmonary rehabilitation for lung cancer patients. Methods From June 2009, comprehensive preoperative pulmonary rehabilitation (CHPR) including intensive nutritional support was performed prospectively using a multidisciplinary team-based approach. Postoperative complication rate and the transitions of pulmonary function in CHPR were compared with historical data of conventional preoperative pulmonary rehabilitation (CVPR) conducted since June 2006. The study population was limited to patients who underwent standard lobectomy. Results Postoperative complication rate in the CVPR (n = 29) and CHPR (n = 21) were 48.3% and 28.6% (p = 0.2428), respectively. Those in patients with Charlson Comorbidity Index scores ≥2 were 68.8% (n = 16) and 27.3% (n = 11), respectively (p = 0.0341) and those in patients with preoperative risk score in Estimation of Physiologic Ability and Surgical Stress scores >0.3 were 57.9% (n = 19) and 21.4% (n = 14), respectively (p = 0.0362). Vital capacities of pre- and post intervention before surgery in the CHPR group were 2.63±0.65 L and 2.75±0.63 L (p = 0.0043), respectively; however, their transition in the CVPR group was not statistically significant (p = 0.6815). Forced expiratory volumes in one second of pre- and post intervention before surgery in the CHPR group were 1.73±0.46 L and 1.87±0.46 L (p = 0.0012), respectively; however, their transition in the CVPR group was not statistically significant (p = 0.6424). Conclusions CHPR appeared to be a beneficial and effective short-term preoperative rehabilitation protocol, especially in patients with poor preoperative conditions.